Peluk: Geolocation of hairdressers under the scrum methodology - Enciso-Quispe, Liliana; Chavez, Edison; Sanmartin, Carlos; Quezada-Sarmiento, Pablo Alejandro; Zelaya-Policarpo, Elmer (2018 13th Iberian Conference on Information Systems and Technologies : 13-16 June 2018, Caceres, Spain, 2018)
As technology develops, the demand for better tools are the order of the day, devices such as: Smartphone, tablets, laptops, PCs allow access to a wide variety of applications and services. The lack of a system that facilitates the georeferencing of beauty salons, which also traces the route from one point to another, and that allows to display information such as your exact address, style, gender, local references, etc. Realizing an investigation of the subject a custom application was created, using tools of last generation, such as: Language of Hypertext Marks 5, language of leaves of styles 3, programming language PHP, JavaScript, database MYSQL, Bootstrap, Bitbucket repository, unlike existing applications in the market this proposal raises: Registration of owners of hairdressers where the owner enters the system and can register, registration of hairdressers, also offers a filtering system of premises where the user can find your beauty salon so that you can classify them in two ways: customer service, that is, the beauty salon serves men, women, children, pets, and on the other hand the classification of the hairdressing salon, if it is modern, classic, casual, etc.